Saliva Suppresses Osteoclastogenesis in Murine Bone Marrow Cultures. (January 2015) - Caballé-Serrano, J.; Cvikl, B.; Bosshardt, D.D.; Buser, D.; Lussi, A.; Gruber, R.
Saliva can reach mineralized surfaces in the oral cavity; however, the relationship between saliva and bone resorption is unclear. Herein, we examined whether saliva affects the process of osteoclastogenesis in vitro. We used murine bone marrow cultures to study osteoclast formation. The addition of fresh sterile saliva eliminated the formation of multinucleated cells that stained positive for tartrate-resistant acid phosphatase (TRAP). In line with the histochemical staining, saliva substantially reduced gene expression of cathepsin K, calcitonin receptor, and TRAP. Addition of saliva led to considerably decreased gene expression of receptor activator of nuclear factor kappa-B (RANK) and, to a lesser extent, that of c-fms. The respective master regulators of osteoclastogenesis (c-fos and NFATc1) and the downstream cell fusion genes (DC-STAMP and Atp6v0d2) showed decreased expression after the addition of saliva. Among the costimulatory molecules for osteoclastogenesis, only OSCAR showed decreased expression. In contrast, CD40, CD80, and CD86—all costimulatory molecules of phagocytic cells—were increasingly expressed with saliva. The phagocytic capacity of the cells was confirmed by latex bead ingestion. Based on these in vitro results, it can be concluded that saliva suppresses osteoclastogenesis and leads to the development of a phagocytic cell phenotype.